Lampu Lalu Lintas Tenaga Surya Dengan Solar Tracking System Kota Pekanbaru - Simbolon, Abdul Rahman; Asral, Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Solar energy is light radiation and heat from the sun that is harnessed to generate electrical energy. Solar cell is one of the examples from solar energy usage and has been spreadly used by global society including application towards traffic light which is the focus in this study. Simply, Solar cell is converting light energy into electrical energy which commonly installed statically with a certain tilt angle. Meanwhile, solar cell installation location geographically has a different maximum tilt angle every month. Solar tracker is a power booster combined with solar panel which could help it to move mechanically to keep upright angle position towards the sun in daily basis. In addition, Data logger system is used to record voltage, current, and power used to load. Through this study, battery with capacity 12V 3,5Ah and solar cell 50WP could enlighten traffic light maximally for 14 hours and 31 minutes by applying solar tracker as well as showed performance increament for 27,18% higher than non-tracker experiment.Keywords: Solar Cell, Solar Tracker, Traffic Light, Data Logger